Eco-design for perovskite solar cells to address future waste challenges and recover valuable materials - Akulenko Elena S.; Hadadian Mahboubeh; Santasalo-Aarnio Annukka; Miettunen Kati (Elsevier Ltd, 2025)
Photovoltaic development should be steered by the circular economy. However, it is not. In case of perovskite photovoltaics even current environmental directives divert from profitably recycling. Here, we study the profitability of noble metals recovery from wasted perovskite solar cells depending on recycling routes. Our results show that substrates play a major role in the recovery of precious metals and in contrast to previous research even recycling carbon-based devices could reach profitability. Going beyond the recovery of valuable elements, our findings show that revival of the perovskite solar cells is strongly dependent on the device architecture, so far viable for mesoscopic structures with carbon back contacts. Perovskite solar cells are still at the development stage, but the window of opportunity to ensure eco-design will close with market entry, and device complexity might compromise profitability recycling and even result in failure of recovery critical materials. Therefore, its eco-design should be prioritized by materials researchers to develop devices, where valuable components can be separated and liberated with safe and low energy processes.